Prescribing Patterns of Continuous Infusions in Nonobese versus Obese Children Admitted to the Pediatric Intensive Care Unit - Johnson, Peter N.; Stephens, Katy; Barker, Philip; Bergeron, Erica; Lim, Sin Yin; Hagemann, Tracy M.; Lewis, Teresa V.; Neely, Stephen; Miller, Jamie L. (Journal of Pediatric Intensive Care, 2019)
This retrospective study compared the continuous infusions prescribed for obese and nonobese children. Ninety-five (13.2%) received an infusion. A greater percentage of obese (n = 42/168) versus nonobese (53/552) children received infusions, p < 0.01. No difference was noted in the median number of infusions between the obese and nonobese groups, 2 versus 2, p = 0.975. The top 20 prescribed infusions included ten (50%) for sedation/analgesia or neuromuscular blockade and six (30%) for hemodynamic support. A literature search was performed for these 20 agents to determine pharmacokinetics, pharmacodynamics, and dosing in obese children and revealed six studies evaluating fentanyl (n = 2), midazolam (n = 1), and propofol (n = 3).
Keywords: obesity; children; pharmacokinetics